RELEVANSI KONSEP PENGAJARAN NABI ADAM DALAM SURAH AL-BAQARAH 31–33 DENGAN TEORI KOGNITIVISME JEAN PIAGET - Ahmad, Muttaqien; Hermanto, Hermanto; Abdul Jabbar, Luqman (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
This study aims to analyze the relevance between the concept of Allah's teaching to Prophet Adam (peace be upon him) in Surah Al-Baqarah verses 31–33 and Jean Piaget's cognitive learning theory. The background of this research is the dichotomy that often separates Islamic epistemology (revelation) from modern psychological theories (reason), even though both share common ground in viewing human potential. The research method used is a literature study with a thematic exegesis and comparative psychological approach. The results show that the concept of Ta'lim al-Asma (teaching of names) received by Prophet Adam aligns with the concepts of schema and symbolic representation in Piaget's theory. Adam's ability to recall and mention the names of objects demonstrates the functioning of cognitive assimilation and accommodation processes. In conclusion, the Qur'an established the foundations of cognitivism long before modern theories developed, confirming that humans are designed as learning beings with cognitive structures ready to acquire knowledge.